A Dedicated Stitch to Allow Early Safe Mobilization Avoiding Drain-Induced Heart Injury - Gomes,Walter J. (2019)
Abstract Placement of a mediastinal drain is a routine procedure following heart surgery. Postoperative bed rest is often imposed due to the fear of potential risk of drain displacement and cardiac injury. We developed an encapsulating stitch as a feasible, effective and low-cost technique, which does not require advanced surgical skills for placement. This simple, novel approach compartmentalizes the drain allowing for safe early mobilization following cardiac surgery.